The Impact of Music on the Sustenance of Democracy in Nigeria - Bello, Ayobami; Ajewole, John (NIU Journal of Social Sciences, 2024)
This paper examines the impact of music on the sustenance of democracy in Nigeria. It discusses music as a vehicle of expression and communication. The paper examines how music is used to mobilize people or rally them to solidarity. The study relies on the survey of selected songs from the albums produced by Nigerian musicians on issues bordering on the sustenance of democracy in Nigeria. The outcome of the study reveals the use of music in the transmission of moral values; transmission of culture; media system; social reconstruction; political solidarity; electoral campaigns; electoral media; esprit de corps; corruption; communal clashes; political office arrangement; government policy; child abuse and women liberation; fight for freedom/anti-Apartheid crusade; social ill and social revaluations and National integration/patriotic song. The study concludes that music is a part of the process of living and has always been part of man. The study recommends that Nigerian albums should be censored before they are waxed to check and prohibit the dissemination of wrong messages to Nigerians. Keywords: Music, Democracy, Nigeria, Function, Song.